Black's law dictionary - Garner, Bryan A.; Black, Henry Campbell (Dallas, Texas, USA Thomson Reuters, 2019)
This edition continues the undertaking begun by Henry Campbell Black in 1891: to marshal legal terms to the fullest possible extent and to define them accurately
Includes bibliographical references (pages 2053-2075) and index.
osc 18/08/2021
Ref
Keywords: Law; Law